WOMEN MALAY RENGAT ENTREPRENEURSHIP (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
The main issue of this research is to find out why Malay women participate in trading in the city of Rengat. The purpose of the study was to find out the motives of Malay women in trading. This research is a qualitative study using the hermeneutics method, where researchers asked for help from 7 informants through in-depth interviews and Focus Discusion Groups with 4 informants, the interviews and Focous Groups Discusion were analyzed and interpreted with meaning. The results of this study are women who take part in entrepreneurship or trade in the city of Rengat because to help the development of the household economy, the factors that trigger the emergence of business are family factors and also because of the impulse of entrepreneurship.